Psychological gender and emotional intelligence in youth female soccer players - Rutkowska, K.; Bergier, J. (Journal of Human Kinetics, 2015)
Many sports (for instance soccer) are stereotypically perceived as a male activity. Even so, more and more women decide to become competitive athletes. Since the theory of sport requires comprehensive explanations and the practice of sport needs clear guidelines, interdisciplinary studies into the nature of sport, including its psychological aspects, are necessary. Analysing the psychological profile of female soccer players, particularly those who are about to become professional athletes, can provide many interesting insights into the specific character of female youth sport and show where improvements can be made in athletic training programmes (especially in mental training). It is therefore important to study psychological gender that determines social behaviours and to analyse female athletes` emotional intelligence. Emotional intelligence is defined as a set of emotional competencies that determine the effectiveness of human behaviours. Psychological gender and emotional intelligence have a significant effect on human adaptability and the efficiency of psychosocial functioning. This research was undertaken with the dual purpose of identifying the psychological gender and emotional intelligence of female soccer players. It involved 54 secondary-school girls, some of whom attended a sports class and others played on the Polish national team. The following tools were used to carry out the research: the Gender Assessment Inventory (IPP [This and the other acronyms derive from the Polish language]-developed by Kuczynska) and the Emotional Intelligence Questionnaire (INTE; created by Jaworowska and Matczak). As shown by the analysis of the results, most female soccer players in the study were androgynous and the level of their emotional intelligence was significantly higher than in other participants. This also seems to point to their significantly greater adaptability. At the same time, the level of emotional intelligence in many players was average or low, which seems insufficient and calls for adequate intervention measures to be taken.